Social Control of the Family on Juvenile Post-Drug Rehabilitation Relapse Behavior - Eliza, Diah Nur (Masyarakat: Jurnal Sosiologi, 2018)
This article discusses social control of families to their children following drug rehabilitation. Juveniles who have completed rehabilitation programs will experience a resocialization process,i.e. socialization to a new environment or the old environment they once left. Previous studies have identified that the juvenile resocialization process after rehabilitation is influenced by the social environment and family factors. The resocialization process, alongside social control from the family, can prevent the behavior of re-using drugs or relapsing. This article is written based on a qualitative research. The primary data are obtained from juveniles aged 12-18 years, not married, and have experienced drug rehabilitation. This article indicate that there is a relationship between emotional bonding and the control of love-oriented discipline. The emotional bonds found in this study tend to be negative with the control of the love-oriented discipline, encouraging the child’s behavior of relapsing. Furthermore, the results of this study indicate that the form of discipline methods used by parents can have different implications for different children, so the form of appropriate control method to the child’s behavior cannot be determined.